PERILAKU ANAK ANAK DALAM KARYA LUKIS REALIS KONTEMPORER - Melani Agusti; Lisa Widiarti (Universitas Negeri Padang, 2021)
Nowadays children's deviant behavior has a negative impact on them and also those around them in a contemporary realist painting. The purpose of this final work is to visualize the expression related to the behavior of children in the city of Padang in Ampang Village, Kuranji District.The method in creating this work uses contemporary realist techniques, namely using mixed techniques, namely a combination of wet and dry techniques, the coloring process using a brush and acrylic cas. In the creation of this painting, it goes through several stages: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Concept Realization, (5) The results of visualizing children's behavior in the city of Padang in this artwork are 10 works with the titles: (1) monopoly 1, (2) monopoly 2, (3) syndrome, (4) affected, (5) addiction, (6) tainted, (7) ego, (8) pensive, (9) sulking , (10) lament.Kata kunci: anak, seni lukis, realis kontemporer.